Treatment modalities for mild class III skeleto-dental malocclusions with anterior crossbite - Reyes, Martin
One can only stress the importance of the adequate contact of the anterior teeth in order to maintain a stable and functional occlusion. Malocclusions which exhibit anterior crossbites provide a unique set of challenges for the orthodontists as they attempt to fix the teeth into their correct incisal relationships. In most instances, the accurate diagnosis of the skeletal pattern will dictate the treatment mechanics. This paper will present four ways to correct his type of malocclusion based on skeletal diagnosis and the timing of treatment.
Keywords: Malocclusion